Kualitas Lingkungan Fisik Kelas dan Hasil Belajar Peserta Didik: Kajian Integratif tentang Pencahayaan, Kebisingan, dan Suhu - Refsi Cahyani; Nur Asiah; Muhammad Muchsin Afriyadi (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
The quality of the physical classroom environment is an external factor that plays an important role in supporting students’ comfort, concentration, and learning outcomes; however, previous studies have tended to examine lighting, noise, and temperature separately. This study aims to analyze and synthesize empirical findings on the effects of classroom lighting, noise, and temperature on students’ learning outcomes and to identify research gaps that require further investigation. This study employed a qualitative approach using an integrative literature review design. Data were collected from relevant peer-reviewed journal articles indexed in international databases or accredited national journals, with accessible DOIs and published between 2018 and 2026. The literature selection process was conducted through identification, screening, eligibility assessment, and final article inclusion, followed by content analysis to identify patterns of findings, conceptual relationships, and each study’s contribution to the research focus. The findings indicate that adequate lighting supports visual comfort, improves focus, and helps students process learning information more effectively. Excessive noise disrupts speech perception, attention, working memory, and material comprehension, while uncomfortable classroom temperature reduces stamina, motivation, and learning concentration. These findings confirm that lighting, noise, and temperature should not be understood as isolated factors, but as interrelated components of the learning environment that shape the quality of students’ learning experiences. The implication of this study is that schools, teachers, and policymakers need to consider the management of the physical classroom environment as part of learning quality improvement strategies through better lighting regulation, noise control, ventilation improvement, and more optimal classroom temperature management.